PENGARUH KUALITAS PELAYANAN DAN PROMOSI PENJUALAN TERHADAP KEPUASAN PENGUNJUNG PLAYTOPIA DI SUN PLAZA KOTA MEDAN - Purba, Mery Lani; Zai, Febi Ferlina; Hutagalung, Yuni Lestina; Nainggolan, Putri Natalia; Tanjung, Povi Andriani; Duha, Penita Hati (JURNAL MUTIARA MANAJEMEN, 2025)
This research aims to determine the partial and simulanous effects of service quality and sales promotions on customer satisfaction at Playtopia in Sun Plaza, Meadn City. A quantitative approach was used as the research methodology. The population of this study consisted of visitors to Playtopia in Sun Plaza, with a sample size of 97 respondents. The analysis findings indicate that, in the partial test, visitor satisfaction is significantly and positively influenced by the factors of service quality and sales promotions. This results of the study indicate that: (1) the service quality variable has a positive and significant effect on visitor satisfaction, with a t-count of 15.532 > t-table of 1.989 and a significance level of 0.01 < 0.05; (2) the sales promotion variable has a positive and significant effect on visitor satisfaction, with a t-count of 3.597 > t-table of 1.989 and a significance level of 0.01 < 0.05. Futhermore, the analysis shows that service quality and sales promotions simultaneously have a positive and significant effect on visitor satisfaction at Playtopia in Sun Plaza, Medan City, as indicated by an F-count of 43.789 > F-table of 3.09 at a significance level of 0.01 < 0.05. based on the coefficient of determination (R2), the two indepnedent factors of service quality and sales promotions account for 0.482 or 48.2% of the variation in the visitor satisfaction variable, while the remaining 51.8% is influenced by other variables not examined in this study.